ESTIMASI TINGKAT KERAWANAN DEMAM BERDARAH DENGUE BERBASIS INFORMASI GEOSPASIAL - Wijaya, Arwan Putra; Sukmono, Abdi (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2017)
Dengue fever is a type of infectious diseases, which often lead to extraordinary events in Indonesia. Kendal is one area which every year has increased the spread of Dengue quite rapidly. The increase in the spread of Dengue in Kendal is largely determined by the decisions taken by the relevant agencies, especially the Department of Health. Prediction incidence of Dengue Fever in Kendal, is still processed manually by the presentation is still limited in the form of tables and graphs, while the presentation in the form of a map has not been done. Rapid changes in land use from agricultural areas into non agricultural areas became one of the causes of the rapid changes in the data.One technology that can provide information on land use and settlement patterns are analyzed with remote sensing. Data from remote sensing, and then combined with several other parameters, such as population density (X1), height of the sea surface (X2),Â  Distance settlement with nearby river (X3) and Distance pemukiaman to the nearest health center (X4) with spatial analysis Geographic Information System (GIS) will be obtained quickly forecast the vulnerability of Dengue Fever.The result showed that the the vulnerability of Dengue fever based spatial analysis Geographic Information System (GIS) scoring method in Kendal in 2015 is divided into three (3) classes, ie areas with low vulnerability level (51297.96 ha / 51, 08%), areas with middle vulnerability level (45176.44 ha / 44, 38%), and areas with high vulnerability level (3947.534 ha / 3, 93 %).